THE INFLUENCE OF THE HOUSE OF REPRESENTATIVES' RIGHT TO INQUIRY ON THE PROCESS OF ORGANIZING HONEST AND FAIR ELECTIONS - Irwansyah; Luthfi Ramadhan (Qaumiyyah: Jurnal Hukum Tata Negara, 2024)
The use of the right of inquiry by The House of Representatives (DPR) in the process of holding general elections has become the subject of heated debate in the Indonesian political context. The right to inquiry allows the DPR to carry out inquiries and investigations into the implementation of elections. This research finds that the use of the DPR's right to inquiry can influence the process of holding elections by increasing transparency and accountability. It is conduct more effective inquiries and investigations into fraud that occurred during the election, so that it can prevent and stop dishonest and unfair actions. Apart from that, it can also strengthen the DPR's supervisory function over the government, so that it can ensure that the government behaves in accordance with applicable laws and regulations. This research also explores the impact of the DPR's use of the right to interrogation on the integrity of the election implementation process. Through quantitative and qualitative data analysis, this research investigates how the implementation of the right to inquiry affects honesty and fairness in general elections. The results show that the right to inquiry has a significant influence, with important implications for democracy and good governance. Abstrak Penggunaan hak angket oleh Dewan Perwakilan Rakyat (DPR) dalam proses penyelenggaraan pemilihan umum (pemilu) telah menjadi subjek perdebatan yang hangat dalam konteks politik Indonesia. Hak angket memungkinkan DPR untuk melakukan penyelidikan dan investigasi terhadap pelaksanaan pemilu yang diduga tidak jujur dan adil. Penelitian ini menemukan bahwa penggunaan hak angket DPR dapat mempengaruhi proses penyelenggaraan pemilu dengan cara meningkatkan transparansi dan akuntabilitas dalam pelaksanaan pemilu. Hak angket memungkinkan DPR untuk melakukan penyelidikan dan investigasi yang lebih efektif terhadap kecurangan yang terjadi selama pemilu, sehingga dapat mencegah dan menghentikan tindakan-tindakan yang tidak jujur dan tidak adil. Selain itu, juga dapat memperkuat fungsi pengawasan DPR terhadap pemerintah, sehingga dapat memastikan bahwa pemerintah berperilaku sesuai dengan hukum dan aturan yang berlaku. Penelitian ini juga mengeksplorasi dampak penggunaan hak interogasi (hak angket) oleh DPR terhadap integritas proses penyelenggaraan pemilu. Melalui analisis data kuantitatif dan kualitatif, penelitian ini menyelidiki bagaimana pelaksanaan hak angket mempengaruhi kejujuran dan keadilan dalam pemilihan umum. Hasil menunjukkan bahwa hak angket memiliki pengaruh signifikan terhadap transparansi dan akuntabilitas pemilu, dengan implikasi penting bagi demokrasi dan good governance.